PENGUATAN LITERASI POLITIK DAN LITERASI MEDIA BAGI GENERASI CERDAS MENUJU PEMILU 2024 - Fitria, Nurul Jannah Lailatul; Rahmadi, Andhi Nur (Sekolah Tinggi Ilmu Ekonomi AMA, 2024)
The 2024 general election is a political democracy through the electoral system. This involves young people who are the largest group of voters. However, the findings in the field are that the younger generation lacks political literacy and media literacy. So there needs to be a socialisation of strengthening political literacy and media literacy for the younger generation. In order to increase the ability and knowledge of the younger generation related to political literacy and media literacy. The activity was aimed at 25 partners. The implementation of the event went well and was classified as on target, on time, and on purpose. As well as showing results according to the target indicators of the success of programme achievements. The results of monitoring and evaluation on the results of the questionnaire show that all partners have strongly agreed on this socialisation event and can be held further events. The interview results showed that partners experienced changes and increased understanding and actions on partners related to political literacy and media literacy. In particular, partners are able and skilled in searching, selecting and disseminating political information appropriately and using social media more wisely and can help the public regarding public information.